A Triangulated Analysis of Scientific-Technological Park Necessity in Colombia’s Sub-Regional Innovation Ecosystems - Hernández Matorel, Moisés David; Lugo Calderón, Nelly Adriana; Pinzón Quiroga, Yina Paola; López Meza, Mayte Guadalupe (Standards-related Regional Innovation and International Cooperation, 2025)
This research highlights a paradox in Colombia’s Science, Technology, and Innovation (STI) system, which has adopted national policies such as CONPES 4069 (2021–2031), continuing to face structural unproductivity, territorial disparities, and institutional fragility, which underscore the emergence of functional regional innovation ecosystems. Positioned within the theoretical frameworks of regional innovation systems, the quadruple helix, and institutional theory, the research explores how scientific-technological parks (STPs) can act as strategic actors for building regional STI capacity in Colombia’s regions. An exploratory design is adopted, the study uses content analysis and data triangulation (literature, Minciencias’ GrupLAC within the SNCTI databases, and the National Competitiveness Report 2024–2025). The findings show a territorial concentration of STI capabilities, with over 60% of recognized research groups and researchers located in four departments (Bogotá-Cundinamarca, Antioquia, Valle del Cauca, and Santander). Only one officially consolidated STP (Parque Tecnológico Guatiguará) exists nationwide, reflecting the gap between policy design and territorial reality. An institutional instability, budgetary contraction, and weak governance mechanisms have undermined the policy coherence required to sustain innovation infrastructure and regional convergence. The analysis concludes that STPs represent not autonomous solutions but potential actors for rebuilding regional innovation. The study contributes to theoretical debates on innovation policy and institutional constraints in developing economies, offering empirical foundations and policy insights for reorienting Colombia’s STI agenda toward regional inclusion and sustainable knowledge-based development.